UNVEILING THE POETIC LANGUAGE OF STUDENT DISCOURSE ON INSTAGRAM - Wedananta, Kadek Adyatna; Purandina, I Putu Yoga (English Review: Journal of English Education, 2023)
This study aims to investigate the poetic function of language used by students on Instagram pertaining to the discourse topics expressed by the students. These researchers adopted a qualitative approach as the research design. This study was conducted by collecting data towards students from schools in Denpasar, Bali, about students' Instagram captions as its document data for analysis. Based on observation, documentation, and interviews with all participants, it can be concluded that Roman Jakobson's poetics function of language, which was demonstrated in the students' Instagram captions, is a viable initiative to discover students’ topics of interest; the students tend to choose topics such as life, love (blossom, broken heart, or loneliness), nature (nature itself or related to humans), personality, wordplay, precious moment,self-confidence, and friendship. These captions are the result of the students' ideology, which include the ideology of wisdom, humor, confession, and hope.